Expediente e Nominata - REVER, Revista (REVER: Revista de Estudos da Religião, 2021)
Nominata de avaliadores: Alexandre Guida Navarro (UNICAMP, Campinas-SP); Carlos F. Dominguez Avila (UNIEURO, Brasília-DF); Carlos Frederico Barboza Souza (PUC Minas, Belo Horizonte-MG); Claudio Santana Pimentel (PUC-SP, São Paulo-SP); Fábio Augusto Darius (UNASP, Capão Redondo-SP); Felipe Yera Barchi (UNESP, São Paulo-SP); Gabriella Barbosa Rodrigues (TAU, Israel); Jefferson Ramalho (PUC-SP, São Paulo-SP); Joana Terezinha Puntel (autônoma); José Petrúcio Farias Júnior (UFPI, Teresina-PI); Mabel Salgado Pereira (CESJF, Juiz de Fora-MG); Matheus Cruz e Zica (UFPB, João Pessoa-PB); Matheus Oliva da Costa (USP, São Paulo-SP); Olivia Bandeira (autônoma); Pedro Paulo Abreu Funari (UNICAMP, Campinas-SP); Valéria Rocha Torres (UNIPINHAL, Espírito Santo do Pinhal-SP)